A new species of Dixonius Bauer, Good, & Branch, 1997 (Squamata: Gekkonidae) from a karstic archipelago in Western Cambodia - L. Lee Grismer; Pablo Sinovas; Evan S. H. Quah; Sothearen Thi; Phyroum Chourn; Sophea Chhin; Seiha Hun; Anthony Cobos; Christian Ching; Matthew L. Murdoch; Jeren J. Gregory; Eddie Nguyen; et al. (Magnolia Press, 2025)
An integrative taxonomic analysis was used to delimit and diagnose a new species of Dixonius from a karstic archipelago in western Cambodia. Dixonius noctivagus sp. Nov. was recovered as the sister species to an undescribed species from eastern Cambodia and southwestern Vietnam based on 1,396 bp of the mitochondrial ND2 gene. A statistically robust diagnosis was established through multivariate and univariate analyses of morphometric, meristic, and categorical color pattern characters separating D. noctivagus sp. Nov. from all other congeners. Although Dixonius is a common and widespread genus, the description herein brings the total number of Dixonius in Cambodia to two—far fewer than the eight species from both neighboring Thailand and Vietnam. this disparity underscores the need for systematic biodiversity surveys in the many understudied regions of Cambodia, particularly focusing on its herpetofauna. the discovery of D. noctivagus sp. Nov. alongside recently described Cyrtodactylus and Hemiphyllodactyus species from the same karst formations highlights the urgent need for legal protection of these fragile habitats in the region.